2018
DOI: 10.2134/jeq2017.07.0265
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Fate of Pathogens during Vermicomposting of Organic Wastes

Abstract: Management of both municipal and industrial organic wastes remains a major threat to biota and the environment due to the presence of pathogens in abundance. Vermicomposting employing earthworms is increasingly gaining attention as a sustainable and ecofriendly technique to transform and sanitize a variety of organic wastes into nutrient-rich biofertilizer. Although considerable research has been undertaken to show that vermicomposting can significantly reduce pathogenic contents, there is little effort to sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…During vermicomposting, interaction between earthworms and microbial population can lead to a reduction in the frequency of potentially pathogenic microbes. Although considerable research studies have been performed to report that vermicomposting can significantly reduce pathogens, there is little effort to summarize various mechanisms causing this process [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During vermicomposting, interaction between earthworms and microbial population can lead to a reduction in the frequency of potentially pathogenic microbes. Although considerable research studies have been performed to report that vermicomposting can significantly reduce pathogens, there is little effort to summarize various mechanisms causing this process [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, decline in pathogens during vermicomposting was mainly selective, and earthworms could have a different effect based on the type. This could be related to whether the pathogen was positive-or negative-gram in terms of cell wall composition [45].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to conventional composting, vermicomposting is a mesophilic process with a temperature below 35°C, and this range enables the growth of worms and pathogenic microorganisms (Khwairakpam and Bhargava, 2009;Swati and Hait, 2018). Vermicomposting achieves sludge stabilization by the synergistic effect between worms and microbial populations (Table 2), and it has been reported that the enzyme activity and endosymbiotic microorganisms of earthworms play an important role (Monroy et al, 2009;Sen and Chandra, 2009;Swati and Hait, 2018). Furthermore, the humate in sludge and gut transport of worms are also involved in pathogen inactivation (Soobhany et al, 2017).…”
Section: Composting and Vermicompostingmentioning
confidence: 99%
“…47 Pathogen inactivation is also affected by technologyspecific factors, including solar radiation intensity in solar drying 48 and digestion by earthworms in vermicomposting. 49 Therefore, the key factors that affect pathogen inactivation need to be identified for target microorganisms and technologies, individually. The heterogeneous nature of excreta matrices distinguishes the modeling for sanitation products from that for food matrices, and thus, we call the modeling approach for excreta matrix predictive "environmental" microbiology.…”
Section: Productsmentioning
confidence: 99%